Urban files from Literature, Utopia, Ideology. - Santuccio, Salvatore (DISEGNARECON, 2014)
During the end of the last century there were many interesting analysis in the history of art, before, and in architecture later, by means of the virtual models. Walking into the world of painting or architecture we felt progress could open new important knowledge in different fields like utopia in architecture. All started from scientific studies: new interests in geometrical rules in drawing reconstruction and the big growth of 3d modelling softwares. But the experiences here presented tell us drawing is not only made by technical knowledge and often it is like a translation in an other language, with results that could be very far from the feeling we had observing the original painting or project we had to translate.